Tree Allometric Equations in South Asia - Sandeep, S.; Sivaram, M.; Matieu, H.; Luca, B.; Rini, G. (Indian Forester, 2016)
Estimation of volume, biomass and carbon stocks support several applications from the commercial exploitation of timber to global carbon cycle. Especially in the latter context the estimation of tree biomass with sufficient accuracy is essential to determine annual changes of carbon stored in particular ecosystems. Under the aegis of UN - REDD programme an extensive database on tree allometry in South Asia (Bangladesh, Bhutan, India, Nepal, Maldives, Pakistan and Sri Lanka) was prepared by extensive and exhaustive literature collected from the region by institutional visits, bibliographic databases and FAO reports. An evaluation of this data on tree allometry in South Asia shows that there exists a total of 4456 equations on volume, biomass, BEF, carbon and other growth variables for 375 species belonging to 96 families and 275 genera. Proportionate allocation of allometric models for different species in the collected documents is not homogenous with commercially important ones capturing more percentage share of equations. Vague description of tree components and output terms reduces the quality of allometric equations developed in the region. Also the geographical distribution of these allometric equations is highly skewed and conscious efforts should be taken to unearth documents on allometry in the neglected life zones.